2010
DOI: 10.1002/pmic.200900633
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression profile of Orientia tsutsugamushi

Abstract: Orientia tsutsugamushi, an obligate intracellular bacterium, is the causative agent of Scrub typhus. The control mechanisms for bacterial gene expression are largely unknown. Here, the global gene expression of O. tsutsugamushi within eukaryotic cells was examined using a microarray and proteomic approaches for the first time. These approaches identified 643 genes, corresponding to approximately 30% of the genes encoded in the genome. The majority of expressed genes belonged to several functional categories in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…2A). This result is partially consistent with our previous report, in which the expression of several ank genes was observed in a microarray-based transcriptome analysis, but no Ank proteins were detected by proteome analysis of the whole bacterial lysate [27]. In the current study, specific but weak antibody responses against only three of nine Ank proteins tested were detected using serum from scrub typhus patients (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…2A). This result is partially consistent with our previous report, in which the expression of several ank genes was observed in a microarray-based transcriptome analysis, but no Ank proteins were detected by proteome analysis of the whole bacterial lysate [27]. In the current study, specific but weak antibody responses against only three of nine Ank proteins tested were detected using serum from scrub typhus patients (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In the whole bacterial proteome analysis, 17 O . tsutsugamushi -specific genes including tsa56 and scaA were identified to be translated [30]. Here, we showed that ScaA, an autotransporter protein of O .…”
Section: Discussionmentioning
confidence: 98%
“…Previously, we reported the whole genome sequence of the O . tsutsugamushi Boryong strain [29] and profiled its global gene expression using a microarray system and proteomic approaches [30]. From our proteomic analysis, we predicted 10 outer membrane proteins unique to O .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we also observed a similar level of sequence variation in the O. tsutsugamushi autotransporter proteins; however, the sequences of each gene were highly conserved between orthologs found in the two different strains (Table 1), suggesting a functional conservation. Recently, it has been reported that the core gene set of the family Rickettsiaceae is highly conserved between the two strains, although amplified repetitive sequences have induced extensive genome shuffling and duplications and deletions of many genes (6,25). Considering the average nucleotide identity of the 541 core genes in the two strains is 97.5% (25), that of four sca gene orthologs is slightly lower (90.8%).…”
Section: Discussionmentioning
confidence: 99%